Use of Healthcare Services Following Severe Hypoglycemia in Patients with Diabetes: Analysis of Real-World Data. Issue 2 (June 2016) - Goldstein, Dalit; Chodick, Gabriel; Shalev, Varda; Thorsted, Brian; Elliott, Lisa; Karasik, Avraham
Abstract Introduction Severe hypoglycemia is a burden for both patients and the healthcare system payer alike. This study aimed to quantify the resource use associated with a severe hypoglycemic event (SHE) in patients with diabetes. Methods This retrospective cohort study compared resource use (e.g., physician visits, hospitalizations, and medications) 1 month pre- and post-SHE among patients with type 1 (T1D) or type 2 diabetes (T2D) from a large not-for-profit healthcare provider. Results From 2005 to 2014, 284 patients with T1D (52.5% male, mean age 29.8 years, mean HbA1c 7.9%) and 3691 patients with T2D (47.6% male, mean age 67.1 years, mean HbA1c 7.3%) were eligible for inclusion in the study. In total, 95.4% of patients with T1D and 32.8% of patients with T2D were insulin treated, while 3.5% of patients with T1D and 70.4% of patients with T2D were treated with oral drugs that could cause hypoglycemia (sulfonylureas or meglitinides). Hospital admissions increased by 95% in T1D and 127% in T2D (P  < 0.001) 1 month post-SHE versus 1 month pre-SHE. Of those admitted to hospital (T1Dn  = 59; T2Dn  = 1214), the mean length of stay was significantly longer during the month post- versus pre-SHE [2.08 vs. 0.88 days, P  = 0.036 (T1D) and 4.17 vs. 1.45 days, P  < 0.001 (T2D)]. Outpatient visits also increased by 37% for T1D and 47% for T2D between these two time periods (P  < 0.001). The total monthly expense per patient increased by 46% and 87% for T1D and T2D, respectively, from $485 pre-SHE to $708 post-SHE for T1D, and from $601 pre-SHE to $1121 post-SHE for T2D (P  < 0.001). The greatest expense was hospital care, with increases of 179% and 166% for T1D and T2D, respectively, to $312 and $706 per patient/month. Conclusion This real-world analysis from a large diabetes registry indicates an increased use of healthcare services, including more frequent and prolonged hospital admissions and outpatient visits after an SHE, which resulted in an increase in healthcare expense. Funding Novo Nordisk.